Odkształcenia Skończone Elementów Sprężystych Sprzęgła Elastycznego - Wesołowski, Z. (Engineering Transactions, 1960)
The object of this paper is to find the characteristic of an elastic coupling. Of the elastic elements of the coupling it is assumed that they are made of an incompressible, originally isotropic material. The state of stress and strain in the elastic elements is determined by the method described in detail in the Ref. [1]. The torque, in function of the length of twist, is given in the integral form and, for the MOONEY material, in the algebraic form.